Carbon nanotube dispersion and its use

The carbon nanotube dispersion with tailored properties addresses dispersibility and elastic modulus issues, resulting in electrodes with improved strength and conductivity for high-performance lithium-ion secondary batteries.

JP7669897B2Pending Publication Date: 2025-04-30TOYO INK MFG CO LTD +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021160281
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-09
Filing Date
2021-09-30
Publication Date
2025-04-30
Estimated Expiration
2041-09-30

AI Technical Summary

Technical Problem

Existing carbon nanotube dispersions struggle with insufficient dispersibility and elastic modulus, limiting the improvement of electrode strength and conductivity in lithium-ion secondary batteries.

Method used

A carbon nanotube dispersion with specific Raman spectrum characteristics, G/D ratio, dispersant content, complex modulus, phase angle, and particle size distribution, combined with a solvent and binder, to achieve high dispersibility and elastic modulus.

Benefits of technology

The solution results in an electrode film with enhanced electrode strength and conductivity, leading to non-aqueous electrolyte secondary batteries with improved rate and cycle characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669897000011
    Figure 0007669897000011
  • Figure 0007669897000001
    Figure 0007669897000001
  • Figure 0007669897000002
    Figure 0007669897000002
Patent Text Reader

Abstract

To provide a carbon nanotube dispersion that has high dispersibility and elastic moduli in order to obtain an electrode film with excellent electrode strength and electrical conductivity, a carbon nanotube resin composition, and mixture slurry, and a nonaqueous electrolyte secondary battery having excellent rate properties and cycle characteristics.SOLUTION: A CNT dispersion includes carbon nanotubes, a dispersant, and a solvent. In a Raman spectrum of a CNT, the CNT has a G / D ratio of 5-100 where G is a maximum peak intensity in a range of 1560-1600 cm-1 and D is a maximum peak intensity in a range of 1310-1350 cm-1. Relative to the CNT 100 pts.mass, a dispersant is contained in a ratio of 30 pts.mass or more and less than 250 pts.mass. The CNT dispersion has a complex modulus of 5 Pa or more and less than 650 Pa and a phase angle of 5° or more and less than 50°. The CNT has a BET specific surface area of 550-1200 m2 / g.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon nanotube dispersion, more specifically to a carbon nanotube dispersion, a resin composition containing the carbon nanotube dispersion and a resin, a composite slurry containing the carbon nanotube dispersion, a resin, and an active material, an electrode film formed by forming the composite slurry into a film, and a nonaqueous electrolyte secondary battery including the electrode film and an electrolyte. [Background technology]

[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, secondary batteries with high energy density and higher capacity are required. Under such a background, non-aqueous electrolyte secondary batteries using a non-aqueous electrolyte, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.

[0003] The negative electrode materials used in these lithium-ion secondary batteries are carbon materials such as graphite, which has a large charge / discharge capacity per unit mass at a base potential close to that of lithium (Li). However, these electrode materials are used to the extent that the charge / discharge capacity per mass is close to the theoretical value, and the energy density per mass of the battery is approaching its limit. Therefore, in order to increase the utilization rate of the electrode, attempts are being made to reduce the conductive additives and binders that do not contribute to the discharge capacity.

[0004] As the conductive assistant, carbon black, ketjen black, fullerene, graphene, fine carbon materials, etc. are used. In particular, carbon nanotubes, which are a type of fine carbon fiber, are widely used. For example, it is known that adding carbon nanotubes to graphite or silicon negative electrodes improves the electrode's conductivity, electrode strength such as adhesion and expansion and contraction properties, and the rate characteristics and cycle characteristics of lithium ion secondary batteries (see, for example, Patent Document 1). Also, studies are being conducted on reducing electrode resistance by adding carbon nanotubes to positive electrodes (see, for example, Patent Document 2 and Patent Document 3). Among them, multi-walled carbon nanotubes with an outer diameter of 10 nm to several tens of nm are relatively inexpensive, and are expected to be put to practical use.

[0005] When carbon nanotubes with a small average outer diameter are used, a conductive network can be efficiently formed with a small amount, and the amount of conductive auxiliary material contained in the positive and negative electrodes of lithium-ion secondary batteries can be reduced. It is also known that the same effect can be obtained when carbon nanotubes with a long fiber length are used. (See, for example, Patent Document 4.) However, carbon nanotubes with these characteristics have a strong cohesive force and are difficult to disperse, so it has not been possible to obtain a carbon nanotube dispersion liquid with sufficient dispersibility.

[0006] Therefore, methods for stabilizing the dispersion of carbon nanotubes using various dispersants have been proposed. For example, dispersion in water and NMP (N-methyl-2-pyrrolidone) using a polymer-based dispersant such as a water-soluble polymer has been proposed (see Patent Document 1, Patent Document 5, and Patent Document 6). In Patent Document 1, single-walled carbon nanotubes are dispersed in a polyvinylpyrrolidone-containing NMP solvent using zirconia beads, but there is a problem that the dispersion time is long and the dispersed particle size of the carbon nanotubes becomes small, and although the conductivity of the electrode is improved, the electrode strength cannot be improved. In Patent Document 5, oxidation-treated double-walled carbon nanotubes are dispersed in an aqueous carboxymethyl cellulose solution using an ultrasonic homogenizer, but it is difficult to disperse the carbon nanotubes at a high concentration in the solvent. In Patent Document 6, single-walled carbon nanotubes are dispersed in a polyvinylpyrrolidone-containing NMP solvent using ultrasonic waves, but it is difficult to disperse the carbon nanotubes at a high concentration in the solvent. In addition, a method for stabilizing the dispersion of multi-walled carbon nanotubes using a nitrile rubber as a dispersant has been proposed (see Patent Document 7). In the cited document 7, it is proposed that the output characteristics of the electrode can be improved by preparing a multi-walled carbon nanotube dispersion having a specific complex elastic modulus. However, with multi-walled carbon nanotubes having an outer diameter of 10 nm or more, the improvement in electrode strength is insufficient, and it is difficult to improve the cycle characteristics of lithium-ion secondary batteries.

[0007] Therefore, obtaining a carbon nanotube dispersion in which single-walled carbon nanotubes are uniformly dispersed in a dispersion medium at a high concentration has been an important challenge for expanding the range of applications. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2020-105316 A [Patent Document 2] JP 2011-70908 A [Patent Document 3] JP 2014-19619 A [Patent Document 4] JP 2012-221672 A [Patent Document 5] JP 2010-254546 A [Patent Document 6] JP 2005-162877 A [Patent Document 7] Special Publication No. 2018-533175 Summary of the Invention [Problem to be solved by the invention]

[0009] The problem to be solved by the present invention is to provide a carbon nanotube dispersion, a carbon nanotube resin composition, and a composite slurry having high dispersibility and elastic modulus in order to obtain an electrode film having excellent electrode strength and electrical conductivity, and more specifically, to provide a non-aqueous electrolyte secondary battery having excellent rate characteristics and cycle characteristics. [Means for solving the problem]

[0010] That is, the present invention relates to a carbon nanotube dispersion liquid containing carbon nanotubes, a dispersant, and a solvent, and characterized in that the following (1) to (4) are satisfied. (1) 1560-1600 cm in the Raman spectrum of carbon nanotubes -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 When the maximum peak intensity within the range is D, the G / D ratio of the carbon nanotube is 5 to 100. (2) The dispersant is contained in an amount of 30 parts by mass or more and less than 250 parts by mass per 100 parts by mass of carbon nanotubes. (3) The complex modulus of the carbon nanotube dispersion at 25°C and a frequency of 1 Hz is 5 Pa or more and less than 650 Pa, and the phase angle is 5° or more and less than 50°. (4) The BET specific surface area of ​​the carbon nanotubes is 550 to 1200 m2 / g

[0011] In addition, the present invention relates to a method for producing carbon nanotubes having a Raman spectrum of 1560 to 1600 cm -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 The carbon nanotube dispersion liquid is characterized in that, when the maximum peak intensity within this range is defined as D, the G / D ratio of the carbon nanotubes is 10 to 50.

[0012] In addition, the present invention is a method for measuring the shear rate of a carbon nanotube dispersion liquid at 25° C. by using a rheometer. -1 ) is 5 Pa·s or more and less than 40 Pa·s.

[0013] The present invention also relates to the carbon nanotube dispersion liquid, wherein a cumulative particle size D10 measured by a dynamic light scattering method is 200 nm or more and less than 500 nm.

[0014] In addition, the present invention relates to a carbon nanotube having a volume resistivity of 1.0×10 -3 Ω cm~1.0×10 -2 The carbon nanotube dispersion liquid has a viscosity of Ω·cm.

[0015] The present invention also relates to the carbon nanotube dispersion liquid, wherein a cumulative particle size D50 measured by a dynamic light scattering method is 500 nm or more and less than 3000 nm.

[0016] The present invention also relates to the carbon nanotube dispersion liquid, wherein the dispersant has a weight average molecular weight of 10,000 to 100,000.

[0017] The present invention also relates to the carbon nanotube dispersion liquid, wherein the solvent contains water.

[0018] The present invention also relates to a carbon nanotube resin composition comprising the carbon nanotube dispersion and a binder.

[0019] The present invention also relates to a composite slurry comprising the carbon nanotube resin composition and an active material.

[0020] The present invention also relates to an electrode film which is a coating film of the composite slurry.

[0021] The present invention also relates to a nonaqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein at least one of the positive electrode and the negative electrode includes the electrode film. Effect of the Invention

[0022] By using the carbon nanotube dispersion of the present invention, a resin composition, a composite slurry, and an electrode film having excellent electrode strength and adhesion can be obtained. Also, a non-aqueous electrolyte secondary battery having excellent rate characteristics and cycle characteristics can be obtained. Therefore, the carbon nanotube dispersion of the present invention can be used in various fields of application where high conductivity and durability are required. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a graph showing the Raman spectra of the carbon nanotubes used in the examples and comparative examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The carbon nanotube dispersion, resin composition, composite slurry, and the electrode film formed by coating the same, and the nonaqueous electrolyte secondary battery of the present invention will be described in detail below.

[0025] (1) Carbon nanotubes The carbon nanotubes of this embodiment are preferably single-walled carbon nanotubes. The single-walled carbon nanotubes may be mixed with multi-walled carbon nanotubes. A single-walled carbon nanotube has a structure in which one layer of graphite is wound, and a multi-walled carbon nanotube has a structure in which two or more layers of graphite are wound.

[0026] The average outer diameter of the carbon nanotubes in this embodiment is 0.5 nm to 5 nm, preferably 1 nm to 3 nm, and more preferably 1 nm to 2 nm. The average outer diameter of the carbon nanotubes can be calculated by observing the morphology of the carbon nanotubes using a transmission electron microscope (manufactured by JEOL Ltd.), measuring the lengths of the minor axes of 100 tubes, and averaging the number of measurements.

[0027] The BET specific surface area of ​​the carbon nanotube of this embodiment is 550 m 2 / g~1200m 2 / g, 600-1200m 2 / g, and 800m 2 / g~1200m 2 / g is more preferable, and 800m 2 / g~1000m 2 It is more preferred that the molecular weight is / g.

[0028] The carbon nanotube of this embodiment has a Raman spectrum of 1560 to 1600 cm -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 When the maximum peak intensity within this range is defined as D, the G / D ratio is preferably 5-100, more preferably 10-50, and further preferably 20-50.

[0029] The volume resistivity of the carbon nanotube of this embodiment is 1.0×10 -3 Ω cm~3.0×10 -2 Ω cm is preferred, and 1.0×10 -3 Ω cm~1.0×10 -2It is more preferable that the volume resistivity is Ω·cm. The volume resistivity of the carbon nanotubes can be measured using a powder resistivity measuring device (Mitsubishi Chemical Analytech Co., Ltd.: Loresta GP Powder Resistivity Measuring System MCP-PD-51).

[0030] The carbon purity of the carbon nanotubes of this embodiment is represented by the content (%) of carbon atoms in the carbon nanotubes. The carbon purity is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, relative to 100% by mass of the carbon nanotubes.

[0031] The amount of metal contained in the carbon nanotube of this embodiment is preferably less than 20% by mass, more preferably less than 10% by mass, and even more preferably less than 5% by mass, based on 100% by mass of the carbon nanotube. Examples of metals contained in the carbon nanotube include metals and metal oxides used as catalysts when synthesizing carbon nanotubes. Specific examples include metals such as cobalt, nickel, aluminum, magnesium, silica, manganese, and molybdenum, metal oxides, and composite oxides thereof.

[0032] The carbon nanotube of this embodiment may be a surface-treated carbon nanotube. The carbon nanotube may also be a carbon nanotube derivative to which a functional group such as a carboxyl group has been added. Carbon nanotubes that encapsulate a substance such as an organic compound, a metal atom, or a fullerene may also be used.

[0033] The carbon nanotubes of this embodiment may be pulverized carbon nanotubes. The pulverization is performed by using a pulverizer containing pulverization media such as beads and steel balls to pulverize the carbon nanotubes without the presence of a liquid substance, and is also called dry pulverization. The pulverization is performed by utilizing the pulverization force or destructive force caused by the collision between pulverization media. The pulverization mainly has the effect of reducing the size of the secondary particles of the carbon nanotubes, and can improve the dispersibility of the carbon nanotubes. As a dry pulverization device, a known method such as a dry attritor, ball mill, vibration mill, or bead mill can be used, and the pulverization time can be set arbitrarily depending on the device.

[0034] The carbon nanotubes of the present embodiment may be carbon nanotubes produced by any method, including, but not limited to, laser ablation, arc discharge, thermal CVD, plasma CVD, and combustion.

[0035] (2) Dispersant The dispersant of the present embodiment is not particularly limited as long as it can disperse and stabilize the carbon nanotubes, and a surfactant or a resin-type dispersant can be used. Surfactants are mainly classified into anionic, cationic, nonionic, and amphoteric. Depending on the characteristics required for dispersing the carbon nanotubes, a suitable type of dispersant can be used in a suitable amount.

[0036] When selecting an anionic surfactant, its type is not particularly limited.Specific examples include, but are not limited to, fatty acid salts, polysulfonates, polycarboxylates, alkyl sulfates, alkylaryl sulfonates, alkylnaphthalenesulfonates, dialkylsulfonates, dialkylsulfosuccinates, alkyl phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkylaryl ether sulfates, naphthalenesulfonic acid formalin condensates, polyoxyethylene alkyl phosphate sulfonates, glycerol borate fatty acid esters, and polyoxyethylene glycerol fatty acid esters.Furthermore, specific examples include, but are not limited to, sodium dodecylbenzenesulfonate, sodium lauric acid sulfate, sodium polyoxyethylene lauryl ether sulfate, polyoxyethylene nonylphenyl ether sulfate, and sodium salt of β-naphthalenesulfonic acid formalin condensates.

[0037] In addition, the cationic surfactant includes alkylamine salts and quaternary ammonium salts.Specific examples include, but are not limited to, stearylamine acetate, trimethyl coconut ammonium chloride, trimethyl beef tallow ammonium chloride, dimethyldioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkyl mercaptopyridine, poly(vinylpyridine)-dodecyl bromide and dodecylbenzyl triethyl ammonium chloride.In addition, the amphoteric surfactant includes, but is not limited to, amino carboxylate salts.

[0038] Examples of nonionic surfactants include, but are not limited to, polyoxyethylene alkyl ethers, polyoxyalkylene derivatives, polyoxyethylene phenyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, and alkyl allyl ethers.Specific examples include, but are not limited to, polyoxyethylene lauryl ethers, sorbitan fatty acid esters, and polyoxyethylene octylphenyl ethers.

[0039] The surfactant to be selected is not limited to a single surfactant. Therefore, it is possible to use a combination of two or more surfactants. For example, a combination of an anionic surfactant and a nonionic surfactant, or a combination of a cationic surfactant and a nonionic surfactant can be used. In this case, it is preferable to use a suitable amount for each surfactant component. As a combination, a combination of an anionic surfactant and a nonionic surfactant is preferable. The anionic surfactant is preferably a polycarboxylate. The nonionic surfactant is preferably polyoxyethylene phenyl ether.

[0040] Specific examples of the resin-type dispersant include cellulose derivatives (cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethylhydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropylmethyl cellulose, carboxymethyl cellulose, etc.), polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polyacrylonitrile polymers, etc. In particular, methyl cellulose, ethyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, and polyacrylonitrile polymers are preferred.

[0041] Carboxymethylcellulose can be used in the form of a salt, such as sodium salt of carboxymethylcellulose, in which the hydroxy group of carboxymethylcellulose is replaced with a sodium carboxymethyl group.

[0042] The dispersant of the present embodiment has a pullulan-equivalent weight average molecular weight of preferably 5,000 to 30,0000, more preferably 10,000 to 10,0000, and even more preferably 10,000 to 50,000. When a dispersant having a moderate weight average molecular weight is used, the adsorption to CNTs is improved, and the stability of the carbon nanotube dispersion is further improved. In addition, when a dispersant exceeding the above range is used, the viscosity of the carbon nanotube dispersion increases, and when a dispersing machine in which the dispersed liquid passes through a narrow flow path such as a nozzle-type high-pressure homogenizer is used, the dispersion efficiency may decrease. In addition to dispersing ability, the resin-type dispersant may have binding ability, and such a resin-type dispersant may be used as a binder, and the same type of resin as the resin-type dispersant may be used as the binder. When the same type of resin as the resin-type dispersant is used as the binder, it is preferable to use a resin with a weight average molecular weight larger than the weight average molecular weight of the resin-type dispersant.

[0043] In addition to the dispersant of the present embodiment, an inorganic base and an inorganic metal salt may be included. The inorganic base and inorganic metal salt are preferably compounds having at least one of an alkali metal and an alkaline earth metal, and more specifically, chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, and borates of alkali metals and alkaline earth metals. Among these, chlorides, hydroxides, and carbonates of alkali metals and alkaline earth metals are preferred in terms of being able to easily supply cations. Examples of hydroxides of alkali metals include lithium hydroxide, sodium hydroxide, and potassium hydroxide. Examples of hydroxides of alkaline earth metals include calcium hydroxide and magnesium hydroxide. Examples of carbonates of alkali metals include lithium carbonate, lithium hydrogen carbonate, sodium carbonate, sodium hydrogen carbonate, potassium carbonate, and potassium hydrogen carbonate. Examples of carbonates of alkaline earth metals include calcium carbonate and magnesium carbonate. Among these, lithium hydroxide, sodium hydroxide, lithium carbonate, and sodium carbonate are more preferred.

[0044] In addition to the dispersant of the present embodiment, an acid may be contained. The addition of an acid may change the charge state in the dispersion system and the balance between the hydrophilic and hydrophobic parts, improving dispersibility. The type of acid is not particularly limited, and one type or a combination of multiple types may be used. Examples of the acid include oxalic acid, lactic acid, citric acid, polyacrylic acid, polystyrene sulfonic acid, acetic acid, malonic acid, hydrochloric acid, nitric acid, sulfuric acid, boric acid, phosphoric acid, etc.

[0045] In addition to the dispersant of the present embodiment, a defoaming agent may be included. Any defoaming agent having a defoaming effect, such as a commercially available defoaming agent, a wetting agent, a hydrophilic organic solvent, or a water-soluble organic solvent, may be used as the defoaming agent. One type of defoaming agent may be used, or a combination of two or more types of defoaming agents may be used. For example, alcohols such as ethanol, propanol, isopropanol, butanol, octyl alcohol, hexadecyl alcohol, acetylene alcohol, ethylene glycol monobutyl ether, methyl cellosolve, butyl cellosolve, propylene glycol monomethyl ether, acetylene glycol, polyoxyalkylene glycol, propylene glycol, and other glycols; Fatty acid esters: diethylene glycol laurate, glycerin monoricinoleate, alkenyl succinic acid derivatives, sorbitol monolaurate, sorbitol trioleate, polyoxyethylene monolaurate, polyoxyethylene sorbitol monolaurate, natural waxes, etc. Amide-based: polyoxyalkylene amide, acrylate polyamine, etc. Phosphate esters: tributyl phosphate, sodium octyl phosphate, etc. Metal soaps: aluminum stearate, calcium oleate, etc. Oils and fats: animal and vegetable oils, sesame oil, castor oil, etc. Mineral oils: kerosene, paraffin, etc. Silicone-based: dimethyl silicone oil, silicone paste, silicone emulsion, organic modified polysiloxane, fluorosilicone oil, etc.

[0046] (3) Solvent The solvent in this embodiment is not particularly limited as long as it can disperse carbon nanotubes, but is preferably water and / or a mixed solvent consisting of one or more water-soluble organic solvents, and more preferably contains water. If water is contained, it is preferably 95% by mass or more, and more preferably 98% by mass or more, based on 100% by mass of the solvent.

[0047] Examples of the water-soluble organic solvent include alcohols (methanol, ethanol, propanol, isopropanol, butanol, isobutanol, secondary butanol, tertiary butanol, benzyl alcohol, etc.), polyhydric alcohols (ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, butylene glycol, hexanediol, pentanediol, glycerin, hexanetriol, thiodiglycol, etc.), polyhydric alcohol ethers (ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, propylene ... ethylene glycol monomethyl ether acetate, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, ethylene glycol monophenyl ether, propylene glycol monophenyl ether, etc.), amines (ethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, morpholine, N-ethylmorpholine, ethylenediamine, diethylenediamine, triethylenetetramine, tetraethylenepentamine, polyethyleneimine, pentamethyldiethylenetriamine, tetramethylpropylenediamine, etc.), amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), tetrahydrofuran, urea, acetonitrile, etc. can be used.

[0048] (4) Carbon nanotube dispersion The carbon nanotube dispersion liquid of this embodiment contains carbon nanotubes, a dispersant, and a solvent.

[0049] The complex modulus of the carbon nanotube dispersion of this embodiment at 25°C and a frequency of 1 Hz is 5 Pa or more and less than 650 Pa, preferably 5 Pa or more and less than 400 Pa, and more preferably 10 Pa or more and less than 400 Pa. The complex modulus of the carbon nanotube dispersion indicates the hardness of the carbon nanotube dispersion, and tends to be smaller as the dispersibility of the carbon nanotubes is better and the viscosity of the carbon nanotube dispersion is lower. On the other hand, when the fiber length of the carbon nanotubes is large, even if the dispersion is good, the complex modulus may be a high value due to the structural viscosity of the carbon nanotubes themselves.

[0050] The phase angle of the carbon nanotube dispersion of this embodiment at 25°C and a frequency of 1 Hz is 5° or more and less than 50°, and more preferably 10° or more and less than 50°. The phase angle means the phase shift of the stress wave when the strain applied to the carbon nanotube dispersion is a sine wave. If it is a pure elastic body, the sine wave will be in phase with the applied strain, and the phase angle will be 0°. On the other hand, if it is a pure viscous body, the stress wave will be 90° advanced. A carbon nanotube dispersion having a complex elastic modulus and a phase angle within the above range has a good dispersed particle size and dispersion state of the carbon nanotubes, and is suitable as a carbon nanotube dispersion for improving electrode strength and conductivity. The complex modulus and phase angle of the carbon nanotube dispersion liquid can be determined by performing dynamic viscoelasticity measurement at 25°C, a frequency of 1Hz, and a strain rate range of 0.01% to 5% using a rheometer with a diameter of 35mm and a 2° cone. If the measured value includes decimal points, round it to the nearest integer according to Rule B of JIS Z8401:1999.

[0051] A well-developed conductive network is formed by uniformly and well-dispersing the carbon nanotubes while maintaining a certain length or more so that the fiber length does not become shorter due to breakage. Therefore, it is not enough for the conductive material dispersion to simply have a low viscosity and good (apparent) dispersibility; it is particularly effective to judge the dispersion state by combining the complex modulus and / or phase angle with conventional indices such as viscosity. By setting the complex modulus and / or phase angle within the above range, a conductive material dispersion with good conductivity and electrode strength can be obtained.

[0052] The viscosity of the carbon nanotube dispersion of this embodiment is measured using a rheometer at a shear rate of 1 (s -1 When measured at a shear rate of 10 (s), the viscosity is preferably 5 Pa·s or more and less than 60 Pa, more preferably 10 Pa·s or more and less than 40 Pa·s, and even more preferably 20 Pa·s or more and less than 40 Pa·s. -1 When measured at a shear rate of 1 (s), the shear pressure is preferably 1 Pa·s or more and less than 10 Pa. -1 ) the dispersibility of the carbon nanotube dispersion can be determined by measuring the shear viscosity in the above range, and the carbon nanotube dispersion has a good dispersed particle size and dispersion state of the carbon nanotubes and is suitable as a carbon nanotube dispersion for improving electrode strength and conductivity. The viscosity of the carbon nanotube dispersion can be determined by leaving the carbon nanotube dispersion in a thermostatic chamber at 25°C for at least 1 hour, thoroughly stirring the carbon nanotube dispersion, and then measuring the shear viscosity at 25°C and at shear rates of 1s-1 and 10s-1 using a rheometer with a 35mm diameter, 2° cone. If the measured value includes decimal points, it is rounded to the nearest integer in accordance with Rule B of JIS Z8401:1999.

[0053] The cumulative particle size D10 of the carbon nanotube dispersion of this embodiment measured by dynamic light scattering is preferably 200 nm or more and less than 500 nm, more preferably 200 nm or more and less than 400 nm, and even more preferably 300 nm or more and less than 400 nm. The cumulative particle size D50 of the carbon nanotube dispersion measured by dynamic light scattering is preferably 500 nm or more and less than 3000 nm, more preferably 500 nm or more and less than 2000 nm, and even more preferably 500 nm or more and less than 1500 nm. The cumulative particle size D10 and D50 of the carbon nanotube dispersion can be measured using a particle size distribution meter (Microtrack Bell Co., Ltd., Nanotrac UPA, model UPA-EX). The particle size measured by dynamic light scattering is correlated with the fiber length of the carbon nanotubes, and the carbon nanotube dispersion having a cumulative particle size D10 in the above range has a good dispersion state of the carbon nanotubes in the dispersion.

[0054] In order to obtain the carbon nanotube dispersion liquid of this embodiment, it is preferable to carry out a treatment for dispersing the carbon nanotubes in a solvent. The dispersing device used for carrying out such a treatment is not particularly limited.

[0055] As the dispersing device, a dispersing machine that is generally used for dispersing pigments, etc., can be used. For example, a mixer such as a disperser, a homomixer, or a planetary mixer, a homogenizer (Advanced Digital Sonifer (registered trademark), MODEL 1 manufactured by BRANSON, Examples of media-type dispersers include 450DA, M-Technique's "Clearmix", PRIMIX's "Filmix", Silverson's "Abramix", etc.), paint conditioners (Red Devil), colloid mills (PUC's "PUC Colloid Mill", IKA's "Colloid Mill MK"), cone mills (IKA's "Cone Mill MKO", etc.), ball mills, sand mills (Shinmaru Enterprises' "Dyno Mill", etc.), attritors, pearl mills (Eirich's "DCP Mill", etc.), and Coball mills; wet jet mills (Zenus's "Zenus PY", Sugino Machine's "Starburst", Nanomizer's "Nanomizer", etc.); M-Technique's "Clear SS-5", Nara Machine's "MICROS", and other media-less dispersers; and other roll mills, but are not limited to these.

[0056] The amount of carbon nanotubes in the carbon nanotube dispersion of this embodiment is preferably 0.2 to 1.5 parts by mass, more preferably 0.4 to 1.2 parts by mass, and more preferably 0.4 to 1.0 parts by mass, per 100 parts by mass of the carbon nanotube dispersion.

[0057] The amount of dispersant used in the carbon nanotube dispersion liquid of this embodiment is preferably 30 parts by mass to 250 parts by mass, more preferably 50 parts by mass to 150 parts by mass, and even more preferably 50 parts by mass to 100 parts by mass, per 100 parts by mass of carbon nanotubes.

[0058] The pH of the carbon nanotube dispersion of this embodiment is preferably 6 to 11, more preferably 7 to 11, further preferably 8 to 11, and particularly preferably 9 to 11. The pH of the carbon nanotube dispersion can be measured using a pH meter (manufactured by Horiba, Ltd., pH METER F-52).

[0059] (5) Binder The binder is a resin that bonds substances such as carbon nanotubes together.

[0060] Examples of the binder of the present embodiment include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as constituent units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, fluororesins; cellulose resins such as carboxymethylcellulose; rubbers such as styrene butadiene rubber and fluororubber; conductive resins such as polyaniline and polyacetylene. Modified bodies, mixtures, and copolymers of these resins are also acceptable. Among these, polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene, carboxymethyl cellulose, styrene butadiene rubber, and polyacrylic acid are preferred.

[0061] Carboxymethyl cellulose as a binder resin preferably has a high viscosity, for example, a viscosity of 500 to 6000 mPa s when a 1% aqueous solution is prepared, and more preferably 1000 to 3000 mPa s. The viscosity of a 1% aqueous solution of carboxymethyl cellulose can be measured at 25°C with a rotor rotation speed of 60 rpm using a B-type viscometer.

[0062] The carboxymethyl cellulose used as the binder resin preferably has a high degree of etherification. For example, the degree of etherification is preferably 0.6 to 1.5, and more preferably 0.8 to 1.2.

[0063] The type and amount ratio of the binder are appropriately selected according to the properties of the coexisting materials such as carbon nanotubes, active material, etc. For example, the amount of carboxymethyl cellulose used is preferably 0.5 to 3.0 mass%, more preferably 1.0 to 2.0 mass%, when the mass of the active material is 100 mass%.

[0064] The styrene-butadiene rubber may be any one generally used as an electrode binder, so long as it is an oil-in-water emulsion. The amount of styrene-butadiene rubber used is preferably 0.5 to 3.0% by mass, more preferably 1.0 to 2.0% by mass, when the mass of the active material is taken as 100% by mass.

[0065] Regarding the amount of polyacrylic acid used, when the mass of the active material is taken as 100 mass %, the proportion of polyacrylic acid is preferably 1 to 25 mass %, and more preferably 5 to 20 mass %.

[0066] Regarding the amount of polyvinylidene fluoride used, when the mass of the active material is taken as 100 mass %, the proportion of polyacrylic acid is preferably 1 to 10 mass %, and more preferably 1 to 5 mass %.

[0067] (5) Carbon nanotube resin composition The carbon nanotube resin composition of the present embodiment contains carbon nanotubes, a dispersant, a solvent, and a binder.

[0068] In order to obtain the carbon nanotube resin composition of the present embodiment, it is preferable to mix and homogenize the carbon nanotube dispersion liquid and the binder. As a mixing method, various conventionally known methods can be used. The carbon nanotube resin composition can be produced using the dispersing device described above for the carbon nanotube dispersion liquid.

[0069] (6) Slurry mixture The composite slurry of the present embodiment contains carbon nanotubes, a dispersant, a solvent, a binder, and an active material. <Active material> The active material in this embodiment is a material that is the basis of a battery reaction. The active material is classified into a positive electrode active material and a negative electrode active material based on the electromotive force.

[0070] The positive electrode active material is not particularly limited, but may be a metal compound such as a metal oxide or metal sulfide capable of doping or intercalating lithium ions, or a conductive polymer. Examples of the material include oxides of transition metals such as Fe, Co, Ni, and Mn, composite oxides with lithium, and inorganic compounds such as transition metal sulfides. Specifically, MnO, VO, VO 13 Examples of the conductive material include transition metal oxide powders such as TiO2, composite oxide powders of lithium and transition metals such as lithium nickel oxide, lithium cobalt oxide, lithium manganate, and lithium manganate having a spinel structure, lithium iron phosphate-based materials that are phosphate compounds having an olivine structure, and transition metal sulfide powders such as TiS2 and FeS. Conductive polymers such as polyaniline, polyacetylene, polypyrrole, and polythiophene can also be used. The above inorganic compounds and organic compounds may also be used in combination.

[0071] The negative electrode active material is not particularly limited as long as it can dope or intercalate lithium ions. For example, metal Li, its alloys such as tin alloys, silicon alloys, and lead alloys, Li X Fe2O3, Li X Fe3O4, Li XWO2 (where x is a number between 0 and 1), metal oxide-based materials such as lithium titanate, lithium vanadate, and lithium silicate, conductive polymer-based materials such as polyacetylene and poly-p-phenylene, amorphous carbonaceous materials such as soft carbon and hard carbon, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, carbon black, mesophase carbon black, resin-fired carbon materials, gas-phase grown carbon fibers, and carbon fibers. These negative electrode active materials can be used alone or in combination of two or more.

[0072] As the negative electrode active material of this embodiment, a silicon-based negative electrode active material, which is a negative electrode active material containing silicon such as a silicon alloy or lithium silicate, is preferable.

[0073] Examples of the silicon-based negative electrode active material include so-called metallurgical grade silicon produced by reducing silicon dioxide with carbon, industrial grade silicon obtained by reducing impurities in metallurgical grade silicon by acid treatment or unidirectional solidification, and high-purity single crystals, polycrystals, amorphous, etc. of different crystal states of high-purity silicon produced from silane obtained by reacting silicon, and silicon with adjusted crystal state and precipitation state obtained by making industrial grade silicon highly pure by sputtering or EB evaporation (electron beam evaporation) methods.

[0074] In addition, silicon oxide, which is a compound of silicon and oxygen, and silicon compounds with various alloys and their crystal states adjusted by a rapid cooling method are also included. Among them, a silicon-based negative electrode active material having a structure in which silicon nanoparticles are dispersed in silicon oxide and the outer side is coated with a carbon film is preferable.

[0075] In addition to the silicon-based negative electrode active material, the negative electrode active material of this embodiment preferably uses amorphous carbonaceous materials such as soft carbon and hard carbon, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite. Among them, it is preferable to use carbonaceous powders such as artificial graphite and natural graphite.

[0076] The amount of the silicon-based negative electrode active material is preferably 3 to 50 mass %, and more preferably 5 to 25 mass %, based on 100 mass % of carbonaceous powder such as artificial graphite or natural graphite.

[0077] The BET specific surface area of ​​the active material of this embodiment is 0.1 to 10 m 2 / g is preferable, and 0.2 to 5m 2 / g is more preferable, and 0.3 to 3m 2 / g is more preferred.

[0078] The average particle size of the active material of the present embodiment is preferably within a range of 0.5 to 50 μm. It is more preferably 2 to 20 μm.The average particle size of the active material as referred to in this specification is the average value of particle sizes measured by an electron microscope.

[0079] (7) Manufacturing method of composite slurry

[0080] The composite slurry of the present embodiment can be prepared by various conventionally known methods, such as a method of adding an active material to a carbon nanotube resin composition, or a method of adding an active material to a carbon nanotube dispersion and then adding a binder.

[0081] In order to obtain the composite slurry of this embodiment, it is preferable to add an active material to the carbon nanotube resin composition and then perform a dispersion process. The dispersion device used for such a process is not particularly limited. The composite slurry can be obtained using the dispersion device described in the carbon nanotube dispersion liquid.

[0082] The amount of the active material in the composite slurry of this embodiment is preferably 20 to 85 parts by mass, more preferably 30 to 75 parts by mass, and further preferably 40 to 70 parts by mass, per 100 parts by mass of the composite slurry.

[0083] The amount of carbon nanotubes in the composite slurry of this embodiment is preferably 0.01 to 10 parts by mass, more preferably 0.02 to 5 parts by mass, and even more preferably 0.03 to 1 part by mass, relative to 100 parts by mass of the active material.

[0084] The amount of the binder in the composite slurry of this embodiment is preferably 0.5 to 30 mass %, more preferably 1 to 25 mass %, and particularly preferably 2 to 20 mass %, relative to 100 mass % of the active material.

[0085] The amount of solid content in the composite slurry of the present embodiment is preferably 30 to 90 mass %, more preferably 30 to 80 mass %, and more preferably 40 to 75 mass %, relative to 100 mass % of the composite slurry.

[0086] (8) Electrode film The electrode film of the present embodiment is formed by forming a composite material slurry, for example, a coating film in which the composite material slurry is coated on a current collector and dried to form an electrode composite material layer.

[0087] The material and shape of the current collector used in the electrode film of this embodiment are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used.

[0088] The method for applying the composite slurry onto the current collector is not particularly limited, and any known method can be used.Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting, and the drying method can be, but is not limited to, standing drying, a blower dryer, a hot air dryer, an infrared heater, or a far infrared heater.

[0089] After coating, the coating may be rolled using a lithographic press, a calendar roll, etc. The thickness of the electrode mixture layer is generally 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.

[0090] (8) Non-aqueous electrolyte secondary battery The nonaqueous electrolyte secondary battery of this embodiment includes a positive electrode, a negative electrode, and an electrolyte.

[0091] The positive electrode can be prepared by coating a composite slurry containing a positive electrode active material on a current collector and drying the coated composite slurry to form an electrode film.

[0092] The negative electrode may be prepared by coating a composite slurry containing a negative electrode active material on a current collector and drying the coated composite slurry to form an electrode film.

[0093] As the electrolyte, various conventionally known electrolytes capable of moving ions can be used. For example, those containing lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be mentioned, but are not limited thereto, and those containing sodium salts or calcium salts can also be used. It is preferable that the electrolyte is dissolved in a non-aqueous solvent and used as an electrolytic solution.

[0094] Examples of non-aqueous solvents include, but are not limited to, carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0095] The nonaqueous electrolyte secondary battery of the present embodiment preferably includes a separator, such as, but not limited to, a polyethylene nonwoven fabric, a polypropylene nonwoven fabric, a polyamide nonwoven fabric, or a hydrophilic nonwoven fabric thereof.

[0096] The structure of the nonaqueous electrolyte secondary battery of the present embodiment is not particularly limited, but is usually composed of a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes according to the purpose of use, such as a paper type, a cylindrical type, a button type, a laminated type, or the like. EXAMPLES

[0097] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "carbon nanotubes" may be abbreviated as "CNT." Unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass."

[0098] <Method of measuring physical properties> The physical properties of the CNTs used in the examples and comparative examples described below were measured by the following methods.

[0099] <G / D ratio of CNT> The CNT was placed on a Raman microscope (XploRA, manufactured by Horiba, Ltd.) and measured using a laser wavelength of 532 nm. The measurement conditions were an acquisition time of 60 seconds, an integration number of 2 times, a neutral density filter of 10%, an objective lens magnification of 20 times, a confocal hole of 500, a slit width of 100 μm, and a measurement wavelength of 100 - 3000 cm -1 The CNT for measurement was separated on a slide glass and flattened using a spatula. Among the obtained peaks, the maximum peak intensity within the spectrum range of 1560 - 1600 cm -1 was defined as G, and the maximum peak intensity within the range of 1310 - 1350 cm -1 was defined as D, and the ratio of G / D was defined as the G / D ratio of CNT.

[0100] <BET specific surface area of CNT> The CNT was weighed using an electronic balance (MSA225S100DI, manufactured by Sartorius) to measure 0.03 g, and then dried while degassing at 110 °C for 15 minutes. Subsequently, the BET specific surface area of the CNT was measured using a fully automatic specific surface area measuring device (HM-model1208, manufactured by MOUNTECH).

[0101] <Average outer diameter of CNT> The CNT was weighed using an electronic balance (MSA225S100DI, manufactured by Sartorius) to measure 0.2 g into a 450 mL SM sample bottle (manufactured by Sansho Co., Ltd.), 200 mL of toluene was added, and an ultrasonic homogenizer (Advanced Digital Sonifer (registered trademark), MODEL 450DA, manufactured by BRANSON) was used to perform a dispersion treatment under ice cooling at an amplitude of 50% for 5 minutes to prepare a CNT dispersion. Subsequently, the CNT dispersion was appropriately diluted, several μL was dropped in the form of a collodion film, dried at room temperature, and then observed directly using a transmission electron microscope (H-7650, manufactured by Hitachi, Ltd.). The observation was performed at a magnification of 50,000 times, and a plurality of photos containing 10 or more CNTs in the field of view were taken, and the outer diameters of 300 arbitrarily extracted CNTs were measured, and the average value was defined as the average outer diameter (nm) of the CNT.

[0102] <Volume resistivity of CNT> Using a powder resistivity measuring device (manufactured by Mitsubishi Chemical Analytech Co., Ltd.: Loresta GP powder resistivity measurement system MCP-PD-51), with a sample mass of 1.2 g, and using a powder probe unit (four-probe ring electrode, electrode interval 5.0 mm, electrode radius 1.0 mm, sample radius 12.5 mm), with the applied voltage limiter set to 90 V, the volume resistivity [Ω·cm] of the conductive powder under various pressures was measured. At a density of 1 g / cm 3 The value of the volume resistivity of CNT at this density was evaluated.

[0103] <Particle size distribution of CNT dispersion> After leaving the CNT dispersion in a thermostatic bath at 25°C for 1 hour or more, the CNT dispersion was thoroughly stirred and diluted, and then the cumulative particle diameters D10 and D50 of the CNT dispersion were measured using a particle size distribution analyzer (manufactured by Microtrac Bel Co., Ltd., Nanotrac UPA, model UPA-EX). The permeability was absorption, the density of CNT was 1.8, and the shape was non-spherical. The refractive index of the solvent was 1.333. During the measurement, the concentration of the CNT dispersion was diluted so that the value of the loading index was in the range of 0.8 to 1.2.

[0104] <Complex elastic modulus and phase angle of CNT dispersion> The complex elastic modulus and phase angle of the CNT dispersion were evaluated by performing dynamic viscoelasticity measurements at 25°C and a frequency of 1 Hz in the range of strain rates from 0.01% to 5% using a rheometer (RheoStress1 rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a cone of diameter 35 mm and 2°.

[0105] <Viscosity of CNT dispersion> After leaving the CNT dispersion in a thermostatic bath at 25°C for 1 hour or more, the CNT dispersion was thoroughly stirred, and then using a rheometer (RheoStress1 rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a cone of diameter 35 mm and 2°, at 25°C, shear rates of 1 s -1 and 10 s -1The shear viscosity was evaluated by measuring the shear viscosity at .

[0106] <Peel strength of electrode film for negative electrode> The negative electrode composite slurry was applied to the electrode using an applicator so that the weight per unit area of ​​the electrode was 8 mg / cm. 2 After coating on copper foil so that the coating was as above, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes. Then, the specimen was cut into two 90mm x 20mm rectangles with the coating direction as the long axis. The peel strength was measured using a tabletop tensile tester (Strograph E3, manufactured by Toyo Seiki Seisakusho Co., Ltd.) and evaluated by a 180-degree peel test method. Specifically, a double-sided tape (No. 5000NS, manufactured by Nitoms Co., Ltd.) measuring 100mm x 30mm was attached to a stainless steel plate, the prepared battery electrode composite layer was attached to the other side of the double-sided tape, and the layer was peeled off while being pulled from the bottom to the top at a constant speed (50mm / min). The average value of the stress at this time was taken as the peel strength.

[0107] <Peel strength of electrode film for positive electrode> The positive electrode composite slurry is applied to the electrode using an applicator so that the weight per unit area is 20 mg / cm 2 After coating on aluminum foil so that the coating was as above, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes. Then, the film was cut into two 90mm x 20mm rectangles with the coating direction as the long axis. Peel strength was measured using a tabletop tensile tester (Strograph E3, manufactured by Toyo Seiki Seisakusho Co., Ltd.) and evaluated by a 180-degree peel test method. Specifically, a double-sided tape (No. 5000NS, manufactured by Nitoms Co., Ltd.) measuring 100mm x 30mm was attached to a stainless steel plate, the prepared battery electrode composite layer was attached to the other side of the double-sided tape, and the layer was peeled off while being pulled from the bottom to the top at a constant speed (50mm / min). The average value of the stress at this time was taken as the peel strength.

[0108] <Preparation of standard positive electrode> First, 93 parts by mass of a positive electrode active material (HED® NCM-111 1100, manufactured by BASF Toda Battery Materials LLC), 4 parts by mass of acetylene black (Denka Black® HS100, manufactured by Denka Co., Ltd.), and 3 parts by mass of PVDF (Kureha Battery Materials Japan Co., Ltd., Kureha KF Polymer W#1300) were mixed into a 150 cm 3 After adding the mixture to a plastic container, the mixture was mixed with a spatula until the powder was uniform. Then, 20.5 parts by mass of NMP was added, and the mixture was stirred with a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310) at 2000 rpm for 30 seconds. Then, the mixture in the plastic container was mixed with a spatula until it was uniform, and the mixture was stirred with the centrifugal mixer at 2000 rpm for 30 seconds. Then, 14.6 parts by mass of NMP was added, and the mixture was stirred with the centrifugal mixer at 2000 rpm for 30 seconds. Finally, the mixture was stirred with a high-speed mixer at 3000 rpm for 10 minutes to obtain a positive electrode composite slurry. Then, the positive electrode composite slurry was applied to an aluminum foil having a thickness of 20 μm as a current collector with an applicator, and then dried in an electric oven at 120° C.±5° C. for 25 minutes to obtain an electrode with a weight per unit area of ​​20 mg / cm. 2 Further, a rolling process was performed using a roll press (3 ton hydraulic roll press, manufactured by Thank Metal Co., Ltd.) to adjust the density of the composite layer to 3.1 g / cm. 3 A standard positive electrode was prepared.

[0109] <Preparation of standard negative electrode> 0.5 parts by mass of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka), 1 part by mass of MAC500LC (carboxymethylcellulose sodium salt Sunrose special type MAC500L, manufactured by Nippon Paper Industries Co., Ltd., non-volatile content 100%), and 98.4 parts by mass of water were added to a plastic container with a capacity of 150 ml, and then the mixture was stirred for 30 seconds at 2000 rpm using a rotation / revolution mixer (Thinky Awatori Rentaro, ARE-310). Furthermore, 87 parts by mass of artificial graphite (CGB-20, manufactured by Nippon Graphite Industries Co., Ltd.) and 10 parts by mass of silicon were added as active materials, and the mixture was stirred for 10 minutes at 3000 rpm using a high-speed stirrer. Next, 3.1 parts by mass of SBR (TRD2001, manufactured by JSR Corporation) was added, and the mixture was stirred for 30 seconds at 2000 rpm using the rotation / revolution mixer to obtain a negative electrode composite slurry. Then, the negative electrode composite slurry was applied to the electrode using an applicator so that the weight per unit area of ​​the electrode was 8 mg / cm. 2 After coating on copper foil so that the thickness was 1.7g / cm, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes. Then, rolling was performed using a roll press (Thank Metal Co., Ltd., 3t hydraulic roll press) to reduce the density of the composite layer to 1.7g / cm. 3 A standard negative electrode was prepared.

[0110] <Evaluation of rate characteristics of lithium-ion secondary batteries> The laminated lithium-ion secondary battery was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant-current constant-voltage charging (cut-off current 1.1mA (0.02C)) was performed with a charge current of 11mA (0.2C) and a charge end voltage of 4.2V, constant-current discharging was performed with a discharge current of 11mA (0.2C) and a discharge end voltage of 2.5V. After repeating this operation three times, constant-current constant-voltage charging (cut-off current (1.1mA0.02C)) was performed with a charge current of 11mA (0.2C) and a charge end voltage of 4.2V, and constant-current discharging was performed at discharge currents of 0.2C and 3C until the discharge end voltage of 2.5V was reached, and the discharge capacity was calculated for each. The rate characteristic can be expressed by the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown in the following formula 1. (Formula 1) Rate characteristic = 3C discharge capacity / 3rd 0.2C discharge capacity × 100 (%)

[0111] <Evaluation of cycle characteristics of lithium-ion secondary batteries> The laminated lithium-ion secondary battery was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant-current constant-voltage charging (cutoff current 1.38mA (0.025C)) was performed with a charge current of 55mA (1C) and a charge end voltage of 4.2V, constant-current discharging was performed with a discharge current of 55mA (1C) and a discharge end voltage of 2.5V. This operation was repeated 200 times. 1C was the current value at which the theoretical capacity of the positive electrode was discharged in 1 hour. The cycle characteristics can be expressed as the ratio of the 3rd 1C discharge capacity at 25°C to the 200th 1C discharge capacity, as shown in the following formula 2. (Formula 2) Cycle characteristics = 3rd 1C discharge capacity / 200th 1C discharge capacity × 100 (%)

[0112] <Synthesis of dispersant (A)> A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 100 parts of acetonitrile and substituted with nitrogen gas. The reaction vessel was heated to 70°C, and a mixture of 85.0 parts of acrylonitrile, 15.0 parts of acrylic acid, and 5.0 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (NOF Corp.; V-65) was added dropwise over 2 hours to carry out a polymerization reaction. After completion of the dropwise addition, the reaction was continued for another hour at 70°C, and then 0.5 parts of perbutyl O was added and the reaction was continued for another hour at 70°C. Thereafter, the conversion rate was confirmed to exceed 98% by measuring the nonvolatile content, and the dispersion medium was completely removed by vacuum concentration to obtain dispersant (A). The weight average molecular weight (Mw) of dispersant (A) was 38,000.

[0113] (Method of measuring weight average molecular weight (Mw)) The weight average molecular weight (Mw) of the prepared dispersant (A) was measured by gel permeation chromatography (GPC) equipped with an RI detector under the following conditions. The molecular weight is a pullulan-equivalent value. Measurement sample: 0.1% by weight aqueous solution Equipment: HLC-8320GPC (Tosoh) Eluent: 0.1M NaCl aqueous solution Column: TSKgel SuperMultiporePW-M (Tosoh) Flow rate: 1.0mL / min Temperature: 25℃ Injection volume: 100μl

[0114] (Method for measuring degree of etherification) 2.0 g of sodium carboxymethylcellulose and 100 mL of methanol nitrate were added to a 300 mL stoppered Erlenmeyer flask, and the flask was shaken for 2 hours to replace sodium carboxymethylcellulose with carboxymethylcellulose. The carboxymethylcellulose was then suction filtered through a glass filter and washed with 200 mL of 80% methanol. The flask was then substituted with 50 mL of anhydrous methanol, suction filtered, and dried at 105°C for 2 hours. 1.0 to 1.5 g of dried carboxymethylcellulose was weighed and placed in a 300 mL stoppered Erlenmeyer flask, and 15 mL of 80% methanol was added to moisten the flask. 50 mL of 1 / 10N sodium hydroxide was added and the flask was shaken for 2 hours. The excess sodium hydroxide was then back-titrated with 1 / 10N sulfuric acid using phenolphthalein as an indicator, and the degree of etherification was calculated according to (Equation 3) and (Equation 4). (Formula 3) A=(50×F1−X×F2) / (Y×10) X: amount of sulfuric acid added, Y: weight of dry carboxymethyl cellulose, F1: factor of sulfuric acid, F2: factor of sodium hydroxide (Equation 4) Degree of etherification = 0.162A / (1-0.058A)

[0115] Table 1 shows the CNTs used in the examples and comparative examples, the outer diameter of the CNTs, the specific surface area of ​​the CNTs, the G / D ratio, and the volume resistivity.

[0116] [Table 1]

[0117] Table 2 shows the dispersants used in the examples, comparative examples, and reference examples.

[0118] [Table 2]

[0119] Example 1 98.25 parts of ion-exchanged water was added to a stainless steel container, and 0.75 parts of dispersant (A) was added while stirring with a disperser, and the mixture was stirred with a disperser until it was uniform. Then, 1 part of CNT (A) was weighed and added while stirring with a disperser, and a square-hole high-shear screen was attached to a high-shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion was performed at a speed of 8,600 rpm until the entire mixture was uniform. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a pass-type dispersion process was performed five times to obtain a CNT dispersion (WA1). The dispersion process was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa.

[0120] (Examples 2 to 15), (Examples 19 to 20), (Comparative Examples 1 to 2) CNT dispersions (WA2 to WF4) were obtained in the same manner as in Example 1, except that the CNT type, CNT addition amount, dispersant type, dispersant addition amount, ion-exchanged water addition amount, and number of passes were changed as shown in Table 3.

[0121] (Example 16) Capacity 150cm 3 Into this plastic container, 4 parts by mass of the CNT dispersion (WA1) prepared in Example 1 and 6 parts by mass of ion-exchanged water were weighed out, and then the mixture was stirred at 2000 rpm for 30 seconds using a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310) to obtain a CNT dispersion (WA13).

[0122] (Example 17) A CNT dispersion (WA14) was obtained in the same manner as in Example 16, except that the CNT dispersion (WA3) produced in Example 3 was used.

[0123] (Example 18) A CNT dispersion (WA15) was obtained in the same manner as in Example 16, except that the CNT dispersion (WA11) prepared in Example 11 was used.

[0124] Example 21 In a polypropylene bottle container, 20 parts of CNT (C) and 480 parts of zirconia beads with a diameter of 8 mm were charged as grinding media, and grinding treatment was performed for 40 minutes using a paint conditioner manufactured by Red Devil. Then, the zirconia beads were separated, and the CNT (C) was recovered. Next, 98.38 parts of ion-exchanged water was added to a stainless steel container, and while stirring with a disperser, 1.13 parts of dispersant (C) was added, and the mixture was stirred with a disperser until it became uniform. Then, 1.5 parts of the recovered CNT (C) was weighed and added while stirring with a disperser, and a square-hole high shear screen was attached to a high shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion was performed at a speed of 8,600 rpm until the entire mixture became uniform. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) via piping, and a pass-type dispersion process was carried out 20 times to obtain a CNT dispersion liquid (WC27). The dispersion process was carried out using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa.

[0125] Example 22 98.40 parts of ion-exchanged water was added to a stainless steel container, and while stirring with a disperser, 0.50 parts of dispersant (C) and 0.10 parts of polyacrylic acid (manufactured by Fujifilm Wako Pure Chemical Industries, molecular weight 25000) were added, and the mixture was stirred with a disperser until it became uniform. Then, 1.0 part of CNT (A) was weighed and added while stirring with a disperser, and a square-hole high-shear screen was attached to a high-shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion was performed at a speed of 8,600 rpm until the entire mixture was uniform. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a pass-type dispersion process was performed 20 times to obtain a CNT dispersion liquid (WA28). The dispersion process was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa.

[0126] Comparative Example 3 A glass bottle (M-140, manufactured by Kashiwa Glass Co., Ltd.) was charged with 1 part of CNT (A), 0.75 parts of dispersant (A), 98.25 parts of ion-exchanged water, and 120 parts of zirconia beads (bead diameter 1.25 mmφ), and the mixture was dispersed for 8 hours using a paint conditioner manufactured by Red Devil Co., Ltd. An attempt was made to separate the zirconia beads, but the viscosity was high and a CNT dispersion liquid could not be obtained.

[0127] (Comparative Examples 4 to 6) Except for changing the CNT addition amount, dispersion time, and bead diameter to those shown in Table 3, the dispersion treatment was performed in the same manner as in Comparative Example 3, and then the zirconia beads were separated to obtain CNT dispersions (WA17 to WA19).

[0128] [Table 3]

[0129] (Example 23) 99.3 parts of NMP was added to a stainless steel container, and while stirring with a disperser, 0.3 parts of dispersant (E) was added, and the mixture was stirred with a disperser until the dispersant (E) was dissolved. Then, 0.4 parts of CNT (A) was weighed and added while stirring with a disperser, and a square hole high shear screen was attached to a high shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion was performed at a speed of 8,600 rpm until the entire mixture was uniform. Next, the liquid to be dispersed was supplied from the stainless steel container to a high pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a pass-type dispersion process was performed 20 times to obtain a CNT dispersion liquid (A20). The dispersion process was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa.

[0130] (Examples 24 to 26) CNT dispersions (A21 to A23) were obtained in the same manner as in Example 23, except that the number of passes was changed to those shown in Table 4.

[0131] Comparative Example 7 A glass bottle (M-140, manufactured by Kashiwa Glass Co., Ltd.) was charged with 0.4 parts of CNT (A), 0.3 parts of dispersant (E), 99.3 parts of NMP, and 120 parts of zirconia beads (bead diameter 1.25 mmφ), and a dispersion treatment was carried out for 8 hours using a paint conditioner manufactured by Red Devil Co., Ltd. After that, the zirconia beads were separated to obtain a CNT dispersion (A24).

[0132] [Table 4]

[0133] Table 5 shows the evaluation results of the CNT dispersions prepared in Examples 1 to 26 and Comparative Examples 1 to 7. The phase angle of the CNT dispersion was evaluated as ◯ (good) when it was 10 or more and less than 50, △ (passable) when it was 5 or more and less than 10, and × (unacceptable) when it was less than 5 or 50 or more. The complex modulus of the CNT dispersion at 25°C and a frequency of 1 Hz was evaluated as ◯ (good) when it was 5 or more and less than 400, △ (passable) when it was 400 or more and less than 650, and × (unacceptable) when it was less than 5. The viscosity of the CNT dispersion was evaluated as ◎ (excellent) when the shear viscosity at a shear rate of 1 was 20 or more and less than 40, ◯ (good) when it was 10 or more and less than 20, or 40 or more and less than 60, △ (passable) when it was 5 or more and less than 10, and × (unacceptable) when it was less than 5. The particle size evaluation of the CNT dispersion liquid was carried out as follows: when the particle size distribution D10 was between 200 and 300, it was rated as ◎ (excellent); when it was between 300 and 500, it was ◯ (good); and when it was less than 200, it was rated as × (unacceptable).

[0134] [Table 5]

[0135] (Example 28) Capacity 150cm 3 Into a plastic container, 0.63 parts by mass of CNT dispersion (WA1), 12.5 parts by mass of an aqueous solution in which 2% by mass of CMC (manufactured by Daicel FineChem Co., Ltd., #1190) was dissolved, and 13.8 parts by mass of ion-exchanged water were weighed. Then, using a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310), the mixture was stirred at 2000 rpm for 30 seconds to obtain a CNT resin composition (WA1). Then, 2.92 parts by mass of silicon monoxide (manufactured by Osaka Titanium Technology Co., Ltd., SILICON MONOOXIDE, SiO 1.3C 5μm) was added, and the mixture was stirred at 2000 rpm for 30 seconds using the centrifugal mixer. Furthermore, 21.44 parts by mass of artificial graphite (manufactured by Nippon Graphite Industries Co., Ltd., CGB-20) was added, and the mixture was stirred at 2000 rpm for 30 seconds using the centrifugal mixer. Thereafter, 0.78 parts by mass of styrene-butadiene emulsion (TRD2001, manufactured by JSR Corporation) was further added, and the mixture was stirred at 2000 rpm for 30 seconds using the planetary centrifugal mixer to obtain a negative electrode mixture slurry (WA1).

[0136] (Examples 29 to 49), (Comparative Examples 8 to 12) CNT resin compositions (WA2 to WA19) and negative electrode composite slurries (WA2 to WA19) were obtained in the same manner as in Example 28, except that the CNT dispersion was changed to that shown in Table 6 and the amount of CNT and ion-exchanged water added was adjusted so that the CNT was 0.025 parts by mass in 100 parts by mass of the composite slurry. The non-volatile content of the negative electrode composite slurry was 48% by mass.

[0137] (Example 50) Capacity 150cm 3 Into the plastic container, 7.0 parts by mass of NMP in which 8% by mass of PVDF (Solef#5130, manufactured by Solvey) was dissolved was weighed. Then, 0.19 parts by mass of CNT dispersion (A20) was added, and the mixture was stirred for 30 seconds at 2000 rpm using a centrifugal mixer (Awatori Rentaro, ARE-310) to obtain a CNT resin composition (A20). Then, 36.9 parts of a positive electrode active material (HED (registered trademark) NCM-111 1100, manufactured by BASF Toda Battery Materials, LLC) was added, and the mixture was stirred for 2.5 minutes at 2000 rpm using the centrifugal mixer to obtain a positive electrode composite slurry (A20).

[0138] (Examples 51 to 53), (Comparative Example 13) Except for changing the CNT dispersion liquid shown in Table 6, the same method as in Example 50 was used to obtain CNT resin compositions (A21 to A24) and positive electrode composite material slurries (A21 to A24).

[0139] [Table 6]

[0140] (Example 54) The negative electrode composite slurry (WA1) was applied to the electrode using an applicator so that the coating weight per unit area was 8 mg / cm 2 After coating on a copper foil so as to obtain a coating, the coating was dried in an electric oven at 120° C.±5° C. for 25 minutes to obtain an electrode film (WA1).

[0141] (Examples 55 to 75), (Comparative Examples 14 to 18) The electrode membranes (WA2) to (WA19) were obtained in the same manner as in Example 54, except that the negative electrode composite slurry shown in Table 7 was used.

[0142] (Example 76) The positive electrode composite slurry (A20) was applied to the electrode using an applicator so that the amount of the electrode per unit area was 20 mg / cm. 2 After that, the coating was dried in an electric oven at 120° C.±5° C. for 25 minutes to obtain an electrode film (A20).

[0143] (Examples 77 to 79), (Comparative Example 19) The electrode films (A21) to (A24) were obtained in the same manner as in Example 76, except that the positive electrode mixture slurry shown in Table 7 was used.

[0144] Table 7 shows the evaluation results of the electrode films produced in Examples 54 to 79 and Comparative Examples 14 to 19. The adhesion evaluation was performed with the following criteria: peel strength (Ω cm) of 0.5 or more was rated as ◎ (excellent), 0.3 to less than 0.5 was rated as ○ (good), 0.1 to less than 0.3 was △ (passable), and less than 0.1 was rated as × (bad).

[0145] [Table 7]

[0146] (Examples 80 to 101), (Comparative Examples 20 to 24) The electrode films (WA1 to WA19) were rolled using a roll press (3 ton hydraulic roll press, manufactured by Thank Metal Co., Ltd.) until the density of the composite layer reached 1.7 g / cm 3 Thus, a negative electrode having the above structure was fabricated.

[0147] (Examples 102 to 105), (Comparative Example 25) The electrode films (A20 to A24) were rolled using a roll press (3 ton hydraulic roll press, manufactured by Thank Metal Co., Ltd.) until the density of the composite layer reached 3.2 g / cm 3 A positive electrode having the following structure was fabricated.

[0148] Table 8 shows the negative electrodes and positive electrodes produced in Examples 80 to 105 and Comparative Examples 20 to 25.

[0149] [Table 8]

[0150] (Example 106) The negative electrode (WA1) and the standard positive electrode were punched out to 50 mm x 45 mm and 45 mm x 40 mm, respectively, and the separator (porous polypropylene film) between them was inserted into an aluminum laminate bag and dried in an electric oven at 60 ° C for 1 hour. After that, in a glove box filled with argon gas, 2 mL of electrolyte (a non-aqueous electrolyte in which ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate were mixed in a ratio of 3:5:2 (volume ratio) to prepare a mixed solvent, and VC (vinylene carbonate) and FEC (fluoroethylene carbonate) were added as additives at 1 part by mass each to 100 parts by mass of the mixed solvent, and LiPF6 was dissolved at a concentration of 1 M) was injected, and the aluminum laminate was sealed to prepare a laminated lithium-ion secondary battery (WA1).

[0151] (Examples 107 to 127), (Comparative Examples 26 to 30) Laminate type lithium ion secondary batteries (WA2 to WA19) were produced in the same manner except that the negative electrode was changed to one shown in Table 9.

[0152] (Example 128) The standard negative electrode and positive electrode (A20) were punched out to 50 mm x 45 mm and 45 mm x 40 mm, respectively, and the separator (porous polypropylene film) between them was inserted into an aluminum laminate bag and dried in an electric oven at 60 ° C for 1 hour. After that, in a glove box filled with argon gas, 2 mL of electrolyte (a non-aqueous electrolyte in which ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate were mixed in a ratio of 3:5:2 (volume ratio) to prepare a mixed solvent, and VC (vinylene carbonate) and FEC (fluoroethylene carbonate) were added as additives at 1 part by mass each to 100 parts by mass of the mixed solvent, and LiPF6 was dissolved at a concentration of 1 M) was injected, and the aluminum laminate was sealed to prepare a laminated lithium ion secondary battery (A20).

[0153] (Examples 129 to 131), (Comparative Example 31) Laminate type lithium ion secondary batteries (A21 to A24) were produced in the same manner except that the positive electrode was changed to one shown in Table 9.

[0154] [Table 9]

[0155] Table 10 shows the evaluation results of the laminated lithium ion secondary batteries produced in Examples 106 to 131 and Comparative Examples 26 to 31. The rate characteristics were rated as ◎ (excellent) when the rate characteristics were 80% or more, ◯ (good) when they were 70% or more and less than 80%, △ (passable) when they were 60% or more and less than 70%, and × (unsatisfactory) when they were less than 60%. The cycle characteristics were rated as ◎ (excellent) when they were 90% or more and less than 90%, ◯ (good) when they were 85% or more and less than 90%, △ (passable) when they were 80% or more and less than 85%, and - (unsatisfactory) when they were less than 80%.

[0156] [Table 10]

[0157] In the above examples, a carbon nanotube dispersion liquid containing carbon nanotubes, a dispersant, and a solvent was used, the G / D ratio of the carbon nanotubes being 5 to 100, the dispersant being 30 parts by mass or more and less than 250 parts by mass per 100 parts by mass of the carbon nanotubes, and the complex modulus of the carbon nanotube dispersion liquid at 25°C and a frequency of 1 Hz being 5 Pa or more and less than 650 Pa, and the phase angle being 5° or more and less than 50°. In the examples, the adhesion of the electrodes tended to be improved compared to the comparative examples. In addition, the conductivity and electrode strength were improved, and thus a lithium ion secondary battery with excellent rate characteristics and cycle characteristics was obtained. Therefore, it was revealed that the present invention can provide a lithium ion secondary battery with high capacity, high output, and high durability that are difficult to achieve with conventional carbon nanotube dispersion liquids.

[0158] Although the present invention has been described above with reference to the embodiment, the present invention is not limited to the above. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the invention.

[0159] Although the present invention has been described above with reference to the embodiment, the present invention is not limited to the above. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the invention.

Claims

1. A carbon nanotube dispersion liquid containing carbon nanotubes, a dispersant, and a solvent, the carbon nanotube dispersion liquid being characterized by satisfying the following (1) to (4): (1) 1560-1600 cm in the Raman spectrum of carbon nanotubes -1 The maximum peak intensity in the range of G, 1310 to 1350 cm -1 When the maximum peak intensity within the range is defined as D, the G / D ratio of the carbon nanotube is 5 to 100. (2) The dispersant is contained in an amount of 30 parts by mass or more and less than 250 parts by mass per 100 parts by mass of carbon nanotubes. (3) The carbon nanotube dispersion has a complex modulus of elasticity at 25° C. and a frequency of 1 Hz of 5 Pa or more and less than 650 Pa, and a phase angle of 5° or more and less than 50°. (4) The BET specific surface area of ​​the carbon nanotubes is 550 to 1200 m 2 / g

2. In the Raman spectrum of carbon nanotubes, -1 The maximum peak intensity in the range of G, 1310 to 1350 cm -1 2. The carbon nanotube dispersion according to claim 1, wherein the G / D ratio of the carbon nanotubes is 10 to 50, where D is the maximum peak intensity within the range.

3. The carbon nanotube dispersion at 25° C. was subjected to a shear rate of 1 (s -1 3. The carbon nanotube dispersion according to claim 1, wherein the viscosity of the dispersion as measured by a 2000 s or more measuring method is 5 Pa·s or more and less than 40 Pa·s.

4. 4. The carbon nanotube dispersion according to claim 1, wherein the cumulative particle size D10 measured by dynamic light scattering is 200 nm or more and less than 500 nm.

5. 5. The carbon nanotube dispersion according to claim 1, wherein a cumulative particle size D50 measured by a dynamic light scattering method is 500 nm or more and less than 3000 nm.

6. 6. The carbon nanotube dispersion according to claim 1, wherein the dispersant has a weight average molecular weight of 10,000 to 100,000.

7. 7. A carbon nanotube resin composition comprising the carbon nanotube dispersion according to claim 1 and a binder.

8. A composite slurry comprising the carbon nanotube resin composition according to claim 7 and an active material.

9. An electrode film which is a coating film of the composite slurry according to claim 8.

10. 10. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein at least one of the positive electrode and the negative electrode contains the electrode film according to claim 9.

Citation Information

Patent Citations

  • Carbon nanotube-dispersed polar organic solvent and method for producing the same

    JP2005162877A

  • Aqueous dispersion of carbon nanotube, electroconductive composite, and method for producing the same

    JP2010254546A

  • Conductive material dispersion liquid, electrode paste, and conductive material coating active substance

    JP2011070908A

  • Conductive agent for lithium ion secondary battery positive electrode and lithium ion secondary battery using the same

    JP2012221672A

  • Fine carbon dispersion liquid and method of producing the same, and electrode paste and electrode for lithium ion battery using the same

    JP2014019619A